Government Failure versus Market Failure : Microeconomics Policy Research and Government Performance - Winston, Clifford, 1952- (Book collections on Project MUSE., 2006)
When should government intervene in market activity? When is it best to let market forces simply take their natural course? How does existing empirical evidence about government performance inform those decisions? Brookings economist Clifford Winston uses these questions to frame a frank empirical assessment of government economic intervention in Government Failure vs.